One-Pot Synthesis of 4H-Chromenes by Tandem Benzylation and Cyclization in the Presence of Sodium Bisulfate on Silica Gel - Aoyama, Tadashi; Yamamoto, Takumi; Miyota, Saki; Hayakawa, Mamiko; Takido, Toshio; Kodomari, Mitsuo (Synlett, 2014)
A simple and efficient method has been developed for the synthesis of 4H-chromenes from o-hydroxybenzylic alcohols and dicarbonyl compounds containing active methylene groups by using silica gel supported sodium bisulfate. Various dicarbonyl compounds such as diketones, keto esters, and keto amides can be used in the synthesis of the 4H-chromenes.
Keywords: cyclizations; benzylations; supported reagents; chromenes; one-pot syntheses